2001
DOI: 10.1128/jb.183.16.4727-4736.2001
|View full text |Cite
|
Sign up to set email alerts
|

matB , a Common Fimbrillin Gene of Escherichia coli , Expressed in a Genetically Conserved, Virulent Clonal Group

Abstract: A novel fimbrial type in Escherichia coli was identified and characterized. The expression of the fimbria was associated with the O18acK1H7 clonal group of E. coli, which cause newborn meningitis and septicemia when grown at low temperature; hence, it was named the Mat (meningitis associated and temperature regulated) fimbria. The fimbriae were purified from a fimA::cat sfaA::Gm fliC::St derivative of the O18K1H7 isolate E. coli IHE 3034. The purified Mat fimbrillin had an apparent molecular mass of 18 kDa and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
129
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(139 citation statements)
references
References 58 publications
4
129
1
5
Order By: Relevance
“…The presence of host cells was not required for ECP production as initially thought, eliminating the hypothesis that eukaryotic cells or a soluble product were triggering signals. In contrast to meningitis-associated E. coli (33), EHEC produced ECP after growth in DMEM at 26°C or 37°C, but not in LB; suggesting that subtle differences in the mechanisms regulating ECP production may exist between different strains. Production of ECP at temperatures Ͻ37°C might have important implications during the life of the organism outside their bovine or human hosts, allowing for their persistence in the environment and contamination of produce.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The presence of host cells was not required for ECP production as initially thought, eliminating the hypothesis that eukaryotic cells or a soluble product were triggering signals. In contrast to meningitis-associated E. coli (33), EHEC produced ECP after growth in DMEM at 26°C or 37°C, but not in LB; suggesting that subtle differences in the mechanisms regulating ECP production may exist between different strains. Production of ECP at temperatures Ͻ37°C might have important implications during the life of the organism outside their bovine or human hosts, allowing for their persistence in the environment and contamination of produce.…”
Section: Discussionmentioning
confidence: 95%
“…Expression of bacterial pili is under the influence of environmental cues and, sometimes, host factors (35). Previously, it was shown that meningitis-associated E. coli strains, but not any other E. coli pathogroups, were able to assemble the EcpA protein (formerly YagZ) into pili named ''Mat'' (meningitisassociated and temperature-regulated pilus) only after growth at 20°C in LB broth (33). EHEC is indeed able to assemble the EcpA protein into pili upon infection of cultured epithelial cells at host temperature, a phenotype that is biologically significant from the host-pathogen interaction standpoint.…”
Section: Demonstration Of Ecp On Ehec O157:h7 Adhering To Host Epithementioning
confidence: 99%
See 3 more Smart Citations